Surgical treatment of macular hole without removal of the internal limiting membrane - A.Yu. Kleimenov; V.N. Kazaikin; М.А. Lipina; A.D. Ozhegov (Офтальмохирургия)
Purpose. To represent new technique of macular hole surgical treatment without removal of the internal limiting membrane. Material and methods. A clinical, functional, anatomical and topographic analysis of the macular hole treatment in 21 eyes (21 patients), operated at the Eye Microsurgery Yekaterinburg Center in the period from January 2023 to January 2024 using technique developed at the Center (without removing the ILM). The follow-up period ranged from 2 weeks to 1 year (7.2±1.1). Results. The minimum diameter of the MH ranged from 118 to 618 (368.9±32.9) μm, the base diameter – from 98 to 1070 (732.2±61.3) μm. Complete closure of the macular hole in the early postoperative period was observed in 20 cases (out of 21; 95.2%). BCVA on the 1st day after surgery ranged from 0.005 to 0.08 (0.01±0.01), 6 months after surgery – from 0.35 to 0.95 (0.63±0.17). Throughout the entire observation period, there was no negative dynamics in the state of the retinal ganglion cell complex relative to the indicators of the normative base. Conclusion. Developed technique for the surgical treatment of full-thickness macular holes without removing the internal limiting membrane has shown high efficiency, does not cause damage to retinal ganglion cells in the early and late postoperative period, provides high functional results and can be used in everyday medical practice.